2020
DOI: 10.1101/2020.08.25.20180182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Serum Prolactin and Metabolic Disorders: a Systematic Review

Abstract: Background: Serum prolactin levels are associated with metabolic disorders. However, the conclusions were inconsistent among published studies. Methods: PubMed, EMBASE, and the Cochrane Library were used to search for studies investigating the association between serum prolactin levels and metabolic disorders. Studies were included and reviewed if they reported the association between serum prolactin and metabolic components (including waist circumference, body weight indexes, blood pressure, blood glucose, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…An expanding body of clinical evidence suggests the involvement of PRL in metabolic homeostasis, encompassing aspects such as body weight regulation and functions within AT and the pancreas. It is also indicated that PRL's effect on metabolic homeostasis largely depends on its circulating concentration [26,27,36]. In contrast to low and very high PRL levels, which have deleterious metabolic consequences, a specific range of PRL values benefits the metabolism.…”
Section: The Effects Of Prolactin On Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…An expanding body of clinical evidence suggests the involvement of PRL in metabolic homeostasis, encompassing aspects such as body weight regulation and functions within AT and the pancreas. It is also indicated that PRL's effect on metabolic homeostasis largely depends on its circulating concentration [26,27,36]. In contrast to low and very high PRL levels, which have deleterious metabolic consequences, a specific range of PRL values benefits the metabolism.…”
Section: The Effects Of Prolactin On Metabolismmentioning
confidence: 99%
“…Interestingly, deficient levels of PRL (≤7 µg/L) have been associated with a similar degree of impairment of metabolic homeostasis [33,37]. Low PRL levels are associated with a higher prevalence of type 2 diabetes (T2D), IR, glucose intolerance, MS, AT dysfunction, ß-cell dysfunction, NAFLD, and cardiovascular events in humans [27,36].…”
Section: The Effects Of Prolactin On Metabolismmentioning
confidence: 99%
See 2 more Smart Citations